Vertical Electrical Sounding Analysis for Local Subsurface Water Bearing Identification Due to Isolated Hill. Case-study: Madurejo Village, Prambanan District, Yogyakarta Province, Indonesia - Eddy Hartantyo (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2020)
In a subsurface aquifer, there is a ‘barrier like’ phenomenon that blocks the flow of water. It will create a subsurface water bearing/dam and potential source for water well drilling. The existence of clay-limestone in the isolated hill in Madurejo village, Prambanan district, Yogyakarta seems to act like a natural groundwater body which is interesting to be analyzed by means of vertical electrical sounding (VES). For this purpose, three VES points measured with 150 meters apart, creating a line from south to north. Maximum distance for AB is 200 meters. We found the shallow unconfined from surface to 4 m depth and confined aquifers from 6 m to 29 m. The geometry of the second aquifer in combination with the existence of isolated hill seems to have a water-bearing structure which is very potential for water resources.